2020
DOI: 10.3390/ijms21082942
|View full text |Cite
|
Sign up to set email alerts
|

The Separation and Characterization of Extracellular Vesicles from Medium Conditioned by Bovine Embryos

Abstract: Extracellular vesicles (EVs) have been identified as one of the communication mechanisms amongst embryos. They are secreted into the embryo culture medium and, as such, represent a source of novel biomarkers for identifying the quality of cells and embryos. However, only small amounts of embryo-conditioned medium are available, which represents a challenge for EV enrichment. Our aim is to assess the suitability of different EV separation methods to retrieve EVs with high specificity and sufficient efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…In the current study, we identified that SEC (qEV IZON™ single column) resulted in some protein aggregates (possibly the lipoproteins). These findings are in agreement with our previous study [ 23 ], in which EVs were isolated from a medium conditioned by bovine embryos by means of SEC but still showed lipoprotein contamination. Similarly, Takov et al [ 27 ] demonstrated that lipoproteins were co-isolated with EVs derived from plasma when SEC is applied.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the current study, we identified that SEC (qEV IZON™ single column) resulted in some protein aggregates (possibly the lipoproteins). These findings are in agreement with our previous study [ 23 ], in which EVs were isolated from a medium conditioned by bovine embryos by means of SEC but still showed lipoprotein contamination. Similarly, Takov et al [ 27 ] demonstrated that lipoproteins were co-isolated with EVs derived from plasma when SEC is applied.…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrated that ODG UC supersedes SEC using qEV IZON™ single column in terms of EV purity and functionality preservation. It was previously demonstrated by our group [ 12 , 23 , 25 ] that ODG UC is superior in conserving EV-associated proteins and RNAs compared with other standard multistep ultracentrifugation protocols and the SEC method. In the current study, we identified that SEC (qEV IZON™ single column) resulted in some protein aggregates (possibly the lipoproteins).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs have been recognized as one of the intercellular communication mechanisms. EVs are lipid membrane vesicles released by cells with a strategic role that includes paracrine or autocrine biological effects in tissue metabolism [70]. They are present in biological fluids and contain several different active biomolecules, such as proteins, nucleic acids and metabolites.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%